2006
DOI: 10.1093/cercor/bhl086
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Handedness, Brain Asymmetries, and Corpus Callosum Size in Chimpanzees (Pan troglodytes)

Abstract: It has been suggested from studies in human subjects that sex, handedness, and brain asymmetries influence variation in corpus callosum (CC) size and these differences reflect the degree of connectivity between homotopic regions of the left and right cerebral hemispheres. Here we report that handedness is associated with variation in the size of the CC in chimpanzees. We further report that variation in brain asymmetries in a cortical region homologous to Broca's area is associated with the size of the CC but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
1
18
0
1
Order By: Relevance
“…This is supported by histological findings showing an absence of significant correlations between the fiber density and the callosal extent (Aboitiz et al, 1992). Based on this premise, the morphology of the CC where it crosses at the midsagittal plane has been studied extensively, in both human and animal brains (Hopkins et al, 2007;Rilling and Insel, 1999). Previous studies reported that the morphology of the CC was associated with gender (Luders et al, 2006), handedness (Witelson, 1989), IQ , cortical asymmetry (Dorion et al, 2000), forebrain volume (Jancke et al, 1997), and functional lateralization (Josse et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
“…This is supported by histological findings showing an absence of significant correlations between the fiber density and the callosal extent (Aboitiz et al, 1992). Based on this premise, the morphology of the CC where it crosses at the midsagittal plane has been studied extensively, in both human and animal brains (Hopkins et al, 2007;Rilling and Insel, 1999). Previous studies reported that the morphology of the CC was associated with gender (Luders et al, 2006), handedness (Witelson, 1989), IQ , cortical asymmetry (Dorion et al, 2000), forebrain volume (Jancke et al, 1997), and functional lateralization (Josse et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
“…Differences in measurement of callosal size, sample size, and whether (or not) the callosal area is adjusted for brain size all likely contribute to the inconsistency of results. In the present study we adjusted the CC area for total brain volume in accordance with Smith (2005), as did Dunham and Hopkins (2006) and Hopkins et al (2007). However, in the present study the partitioning of the CC was based on DTI tractography (Phillips & Hopkins, 2012), whereas the previous studies employed a geometrically based method (Witelson, 1989).…”
Section: Discussionmentioning
confidence: 97%
“…Handedness may have differential effects on the corpus callosum with age. Prior work has demonstrated that less strongly handed and left-handed individuals have larger corpus callosa [16][18], [53]. In young adults, less strongly lateralized individuals show more ipsilateral MEPs, perhaps due to decreased interhemispheric inhibition (IHI).…”
Section: Discussionmentioning
confidence: 99%